Positive electrode material and preparation method thereof, positive plate, battery and electronic equipment

By using a three-dimensional solid foam graphene layer on the positive electrode material of lithium-ion battery, the problem of poor conductivity and rate performance in the prior art is solved, and higher conductivity and rate performance are achieved.

CN119786546APending Publication Date: 2025-04-08BYD CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411189782.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The conductivity and rate performance of the positive electrode materials of the existing lithium-ion battery are still poor, mainly due to the small contact area between the carbon layer and the positive electrode materials, poor tightness, and uneven coating effect.

Method used

The positive electrode active material matrix is ​​fully covered with a three-dimensional solid foam graphene layer to form a conductive network, and the molding and coating effect of the graphene layer is ensured through specific preparation methods such as chemical foaming.

Benefits of technology

The conductivity and rate performance of the positive electrode material are significantly improved, and the conductivity and stability of the positive electrode material is enhanced through a full-coverage conductive network and face-to-point coverage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786546A_ABST
    Figure CN119786546A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material and a preparation method thereof, a positive plate, a battery and electronic equipment, the positive electrode material comprises a positive electrode active material matrix and a three-dimensional solid foamed graphene layer, the three-dimensional solid foamed graphene layer is provided with a closed cavity, and the positive electrode active material matrix is accommodated in the closed cavity. The positive electrode material provided by the invention can solve the problems that in the prior art, the coating effect is still poor, and the conductivity and the rate capability of a battery still need to be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries and relates to a positive electrode material, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet, a battery, and an electronic device. Background Art

[0002] The positive electrode material of lithium-ion batteries is generally a semiconductor material. The carrier diffusion coefficient inside the material is very low, and the electronic conductivity is relatively low. For example, the electronic conductivity of lithium iron phosphate is only 10 -9 S cm 2 , which severely limits the performance of lithium-ion batteries. Existing methods for improving conductivity include: nano-sizing, doping and coating, among which coating with carbon materials is the most common method, which can improve the conductivity of the positive electrode material while ensuring that the positive electrode material is not corroded and dissolved during the cycle.

[0003] Surface carbon coating is a commonly used coating method in industry. Glucose and PEG (polyethylene glycol) are usually used as carbon sources to coat the surface of the positive electrode material through processes such as sanding and heat treatment. However, the coating in the existing coating technology is point-to-point coating. The contact area between the carbon layer and the positive electrode material is small, the tightness is poor, and the uniformity of the coating cannot be determined, which reduces the overall coating effect, and the conductivity and rate performance are still poor.

[0004] Therefore, it is urgent to develop a positive electrode material with higher conductivity and better rate performance. Summary of the invention

[0005] The present invention provides a positive electrode material for solving the problem that the coating effect in the prior art is still poor, and the conductivity and rate performance of the battery still need to be improved.

[0006] The present invention provides a method for preparing a positive electrode material. The method is simple and easy to implement, and can prepare a positive electrode material in which a positive electrode active material matrix is ​​completely coated in a graphene layer, thereby improving the conductivity and rate performance of a battery.

[0007] The present invention provides a positive electrode sheet, comprising the positive electrode material or the positive electrode material prepared by the above preparation method.

[0008] The present invention provides a battery, comprising the positive electrode sheet.

[0009] The present invention provides an electronic device, comprising the battery.

[0010] On one hand, the present invention provides a positive electrode material, including a positive electrode active material matrix and a three-dimensional solid foamed graphene layer, wherein the three-dimensional solid foamed graphene layer has a closed cavity, and the positive electrode active material matrix is ​​accommodated in the closed cavity.

[0011] In the positive electrode material as described above, the thickness of the three-dimensional solid foamed graphene layer is 0.3-0.4 nm.

[0012] In the positive electrode material as described above, the maximum size of the closed cavity is 50 to 150 μm.

[0013] The positive electrode material as described above has a specific surface area of ​​20 to 50 m 2 / g.

[0014] In the positive electrode material as described above, the mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​1:(20-40).

[0015] The positive electrode material as described above, wherein the positive electrode active material matrix comprises at least one of lithium metal phosphate and lithium transition metal oxide;

[0016] Wherein, the general chemical formula of the lithium metal phosphate is LiMPO4; M is selected from at least one of Fe, Co, Ni, Cr, and Zn;

[0017] The general chemical formula of the lithium transition metal oxide is Li 1+a [Ni x Co y M 1 z M 2 w ] 1-a O2; 0≤a≤0.2, 0.3≤x≤1, 0≤y≤0.4, 0≤z≤0.4, 0≤w≤0.1, and x+y+z+w=1, M 1 At least one selected from Mn and Al, M 2 At least one selected from Al, Ti, Mg, Zr, W, Y, Sr, Co, F, Si, Na, Cu, Fe, Ca, S and B.

[0018] Another aspect of the present invention provides a method for preparing the positive electrode material as described above, comprising the following steps:

[0019] (1) mixing and grinding a raw material system including a cathode active material matrix, cysteine ​​and phytic acid to obtain a uniformly mixed and viscous brown colloid, and pre-curing the colloid to obtain a cathode material precursor;

[0020] (2) calcining the positive electrode material precursor to obtain the positive electrode material.

[0021] In the preparation method as described above, the mass ratio of the positive electrode active material matrix to cysteine ​​and phytic acid is (1): (4-6): (20-30); and / or,

[0022] The pre-curing treatment temperature is 60-80°C and the time is 10-30 minutes; and / or,

[0023] The calcination treatment temperature is 500-600° C., the time is 2-3 hours, the heating rate is 5-10° C. / min, and the calcination atmosphere includes at least one of N2 and H2.

[0024] Another aspect of the present invention provides a method for preparing the positive electrode material as described above, comprising the following steps:

[0025] (1) grinding a positive electrode active material matrix and a carbon source, adding a foaming agent, and mechanically stirring to generate bubbles, and then standing and pre-curing to obtain a positive electrode material precursor;

[0026] (2) The positive electrode material precursor is calcined at a temperature of 500-800° C. for 1-2 hours to obtain the positive electrode material.

[0027] In the preparation method as described above, the carbon source is selected from at least one of glucose and polyethylene glycol.

[0028] In the preparation method as described above, the foaming agent includes at least one of a physical foaming agent, a surfactant foaming agent or a chemical foaming agent.

[0029] In the preparation method as described above, the physical foaming agent includes at least one of N2 and Co; and / or,

[0030] The surfactant foaming agent includes at least one of rosin soap foaming agents, plant and animal protein foaming agents, sodium dodecyl sulfonate, and sodium polyoxyethylene fatty alcohol ether sulfate; and / or,

[0031] The chemical foaming agent includes at least one of an azo compound, an N-nitroso compound and a hydrazide compound.

[0032] In the preparation method as described above, the foaming agent is a solid foaming agent or a liquid foaming agent, wherein the sublimation point of the solid foaming agent is 70-100°C, and the boiling point of the liquid foaming agent is less than 110°C.

[0033] In the preparation method as described above, the solid foaming agent includes at least one of azodicarbonamide and sodium α-olefin sulfonate; and the liquid foaming agent includes at least one of pentane and hexane.

[0034] In the preparation method as described above, the mass ratio of the positive electrode active material matrix to the carbon source and the foaming agent is (100): (2-5): (0.3-0.8); and / or,

[0035] The pre-curing treatment temperature is 25-70°C and the time is 30-60 minutes; and / or,

[0036] The calcination treatment temperature is 500-800°C, the time is 1-2h, the heating rate is 5-10°C / min, and the calcination atmosphere includes at least one of N2 and CO.

[0037] In another aspect, the present invention provides a positive electrode sheet, comprising the positive electrode material as described above or the positive electrode material prepared by the preparation method as described above.

[0038] Another aspect of the present invention provides a battery, comprising the positive electrode sheet as described above.

[0039] Another aspect of the present invention provides an electronic device, comprising the battery as described above.

[0040] The present invention provides a positive electrode material, which constructs a fully covered conductive network through a three-dimensional solid foamed graphene layer, and realizes comprehensive surface-to-surface coating of a positive electrode active material matrix, thereby improving the conductivity and rate performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is the SEM characterization of the positive electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] In a first aspect, the present invention provides a positive electrode material, comprising a positive electrode active material matrix and a three-dimensional solid foamed graphene layer, wherein the three-dimensional solid foamed graphene layer has a closed cavity, and the positive electrode active material matrix is ​​accommodated in the closed cavity.

[0044] At present, the commonly used surface carbon coating is to coat the carbon source on the surface of the positive electrode active material through mixing, calcination and other processes, but this can only achieve point-to-point coating. Some carbon materials are attached to the surface of the positive electrode active material particles and are easy to fall off. The contact area between the carbon layer and the positive electrode active material is small and the tightness is poor.

[0045] Therefore, the present invention provides a positive electrode material, including a positive electrode active material matrix and a three-dimensional solid foamed graphene layer. The three-dimensional solid foamed graphene layer has a more open surface and good flexibility, which improves the electrical conductivity of the positive electrode material. The three-dimensional solid foamed graphene layer has a closed cavity, and the positive electrode active material matrix is ​​accommodated in the closed cavity. A conductive network is effectively constructed through the three-dimensional solid foamed graphene layer, and the positive electrode active material matrix is ​​fully coated with points on the surface, so that the contact between the positive electrode active material matrix particles and between the particles and the graphene layer is more sufficient, which effectively reduces the resistance and makes the positive electrode material have higher electrical conductivity and rate performance.

[0046] The present invention provides a positive electrode material, which constructs a fully covered conductive network through a three-dimensional solid foamed graphene layer, and realizes comprehensive surface-to-surface coating of a positive electrode active material matrix, thereby improving the conductivity and rate performance of the positive electrode material.

[0047] Furthermore, the thickness of the three-dimensional solid foamed graphene layer is 0.3-0.4 nm.

[0048] The thickness of the three-dimensional solid foam-like graphene layer can be detected by TEM / SEM.

[0049] The thickness of the coated graphene layer has a significant impact on battery performance. Appropriate control of the thickness of the graphene layer can effectively improve the conductivity and stability of the positive electrode material. By further limiting the thickness of the three-dimensional solid foam-like graphene layer, it can provide an excellent electron conduction path and reduce resistance, thereby improving the battery's rate performance and conductivity.

[0050] In a specific embodiment, the maximum dimension of the closed cavity is 50-150 μm.

[0051] The size of the closed cells can be checked by SEM.

[0052] By limiting the size and volume of the closed cavity, the ion transmission path between the positive electrode active material and the graphene layer can be further improved, and the conductive performance of the conductive network can be further optimized.

[0053] Furthermore, the specific surface area of ​​the positive electrode material is 20 to 50 m 2 / g.

[0054] The specific surface area of ​​the positive electrode material can be detected by BET test.

[0055] By limiting the specific surface area of ​​the positive electrode material, the active sites of the reaction can be further increased, the energy density of the positive electrode material can be further improved, and the rate performance and conductivity of the positive electrode material can be improved.

[0056] In a specific embodiment, the mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​1:(20-40).

[0057] The mass ratio of the three-dimensional solid foam-like graphene layer to the positive electrode active material matrix can be detected by XRD.

[0058] By limiting the mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix, the rate performance and conductivity of the positive electrode material can be further improved.

[0059] Further, in a specific embodiment of the present invention, the cathode active material matrix includes at least one of lithium metal phosphate and lithium transition metal oxide; wherein the general chemical formula of the lithium metal phosphate is LiMPO4; M is selected from at least one of Fe, Co, Ni, Cr, and Zn; and the general chemical formula of the lithium transition metal oxide is Li 1+a [Ni x Co y M 1 z M 2 w ] 1-a O2; 0≤a≤0.2, 0.3≤x≤1, 0≤y≤0.4, 0≤z≤0.4, 0≤w≤0.1, and x+y+z+w=1, M 1 The invention comprises at least one selected from Mn and Al, wherein M 2 Includes at least one selected from Al, Ti, Mg, Zr, W, Y, Sr, Co, F, Si, Na, Cu, Fe, Ca, S and B.

[0060] When the positive electrode active material matrix includes at least one of the lithium metal phosphate and the lithium transition metal oxide as described above, the rate performance and the conductivity of the positive electrode material can be further improved.

[0061] In a second aspect, a method for preparing the positive electrode material of the first aspect comprises the following steps:

[0062] (1) mixing and grinding a raw material system including a cathode active material matrix, cysteine ​​and phytic acid to obtain a colloid, and pre-curing the colloid to obtain a cathode material precursor;

[0063] (2) calcining the positive electrode material precursor to obtain the positive electrode material.

[0064] Specifically, in step (1), a cathode active material matrix is ​​placed in a mortar, fully ground, and then cysteine ​​is added to continue grinding until there are no particles and the mixture is evenly mixed with the cathode active material matrix. Finally, phytic acid is added to continue grinding until the color of the mixture changes from purple to brown colloid, and then grinding is stopped; the colloid is transferred to a crucible magnetic boat and placed in a drying oven for pre-curing treatment. Cysteine ​​and phytic acid are used as both carbon sources and foaming agents. After being evenly mixed with the cathode active material matrix, a cathode material precursor is obtained; the mixed grinding treatment and pre-curing treatment are beneficial to improving the molecular weight and viscosity of the system, stabilizing the pores, and shortening the time for the system to reach the gel point, which means that the pore growth time is shortened, which is beneficial to forming smaller pores;

[0065] In step (2), the cathode material precursor is calcined, and the mixture of phytic acid and cysteine ​​reacts under high temperature to produce a large amount of continuous gas, thereby forming a three-dimensional solid foam graphene layer to obtain the cathode material.

[0066] The preparation method of the positive electrode material provided in the present application uses a chemical foaming method to make phytic acid and cysteine ​​both as a carbon source and a foaming agent. Compared with traditional carbon sources, it has the characteristics of better chemical stability, high electrical conductivity, low density and low price. It can produce a positive electrode material with a three-dimensional solid foamed graphene layer that achieves comprehensive surface-to-surface point coating on the positive electrode active material matrix, so that the contact between the positive electrode active material matrix particles and between the particles and the graphene layer is more sufficient, so that the positive electrode material has higher electrical conductivity and rate performance.

[0067] In one specific embodiment, the mass ratio of the positive electrode active material matrix to cysteine ​​and phytic acid is (1): (4-6): (20-30);

[0068] The pre-curing treatment temperature is 60-80°C and the time is 10-30 minutes;

[0069] The calcination treatment temperature is 200-400°C, the time is 2-4, the heating rate is 5-10°C / min, and the calcination atmosphere includes at least one of N2 and CO.

[0070] By further limiting the range of each process parameter in the preparation method, the thickness, specific surface area and other related parameters of the obtained three-dimensional solid foam graphene layer can be further controlled, and the conductivity and rate performance of the positive electrode material can be further improved.

[0071] The present invention also provides another method for preparing the positive electrode material of the first aspect, comprising the following steps:

[0072] (1) grinding a positive electrode active material matrix and a carbon source thoroughly, adding a foaming agent, and mechanically stirring the mixture to generate bubbles, and then allowing the mixture to stand for pre-curing to obtain a positive electrode material precursor;

[0073] (2) The positive electrode material precursor is calcined at a temperature of 500-800° C. for 1-2 h to obtain a positive electrode material.

[0074] In detail, in step (1), the positive electrode active material matrix and the carbon source are fully ground to ensure uniform mixing of the materials, and then a foaming agent is added. Under the action of mechanical stirring, the foaming agent is evenly distributed in the mixture and a large number of bubbles are quickly generated. The mixture is then allowed to stand to stabilize the generated bubbles, and a pre-curing treatment is performed to form a positive electrode material precursor with a certain pore structure.

[0075] In step (2), the precursor material is calcined at 500-800° C. for 1-2 h to obtain the positive electrode material.

[0076] The above preparation method can prepare a positive electrode material with excellent electrical conductivity and rate performance.

[0077] In a specific embodiment, the carbon source is selected from at least one of glucose and polyethylene glycol.

[0078] The three-dimensional solid foam graphene layer prepared by the above carbon source can better shape the graphene layer and further improve the conductivity and rate performance of the positive electrode material.

[0079] Optionally, the foaming agent is at least one of a physical foaming agent, a surfactant foaming agent or a chemical foaming agent.

[0080] Among them, physical foaming agents disperse the gas evenly through mechanical stirring and other methods to form a foam structure, or inject the physical foaming agent into the material under high pressure and then expand the gas to form foam by rapidly reducing the pressure; surfactant foaming agents promote the formation and stabilization of bubbles by reducing the surface tension of the liquid; chemical foaming agents decompose during heating or chemical reaction to release gas to form foam.

[0081] In a specific embodiment, the physical foaming agent includes at least one of N2 and Co, the surfactant foaming agent includes at least one of rosin soap foaming agent, animal and plant protein foaming agent, sodium dodecyl sulfate, and fatty alcohol polyoxyethylene ether sodium sulfate; the chemical foaming agent includes at least one of azo compounds, N-nitroso compounds and hydrazide compounds.

[0082] In another specific embodiment, the foaming agent is a solid foaming agent or a liquid foaming agent, wherein the sublimation point of the solid foaming agent is 70-100°C, and the boiling point of the liquid foaming agent is less than 110°C.

[0083] In detail, the sublimation point of the solid foaming agent includes but is not limited to 70° C., 75° C., 80° C., 85° C., 90° C., 95° C., 100° C. or a range between any two thereof.

[0084] The boiling point of the liquid blowing agent includes, but is not limited to, 105°C, 100°C, 95°C, 90°C, 80°C, 85°C or any other range less than 100°C.

[0085] When the sublimation point of the solid foaming agent and the boiling point of the liquid foaming agent are within the above range, bubbles can be generated at a relatively low temperature, which is beneficial to controlling the formation of the pore structure and laying the foundation for preparing positive electrode materials with higher rate performance and electrical conductivity.

[0086] Optionally, the solid foaming agent includes at least one of azodicarbonamide and sodium α-olefin sulfonate; the liquid foaming agent includes at least one of pentane and hexane.

[0087] Furthermore, the mass ratio of the positive electrode active material matrix to the carbon source and the foaming agent is (100): (2-5): (0.3-0.8); and / or the pre-curing treatment temperature is 25-70°C and the time is 30-60 min; and / or the calcination treatment temperature is 500-800°C, the time is 1-2 h, the heating rate is 5-10°C / min, and the calcination atmosphere includes at least one of N2 and CO.

[0088] By further limiting the range of each process parameter in the preparation method, the thickness, specific surface area and other related parameters of the obtained three-dimensional solid foam graphene layer can be further controlled, and the conductivity and rate performance of the positive electrode material can be further improved.

[0089] In a third aspect, the present invention provides a positive electrode sheet, comprising the positive electrode material of the first aspect or the positive electrode material prepared by the preparation method of the second aspect.

[0090] The positive electrode sheet provided by the present invention includes a positive electrode material, which includes a positive electrode active material matrix and a three-dimensional solid foamed graphene layer. The three-dimensional solid foamed graphene layer has a more open surface and good flexibility, which improves the electrical conductivity of the positive electrode material. The three-dimensional solid foamed graphene layer has a closed cavity, and the positive electrode active material matrix is ​​accommodated in the closed cavity. A conductive network is effectively constructed through the three-dimensional solid foamed graphene layer, and the positive electrode active material matrix is ​​fully coated with a surface, so that the contact between the positive electrode active material matrix particles and between the particles and the graphene layer is more sufficient, which effectively reduces the resistance and makes the positive electrode sheet have higher electrical conductivity and rate performance.

[0091] In a fourth aspect, the present invention provides a battery, comprising the positive electrode sheet of the third aspect.

[0092] The battery provided by the invention has higher electrical conductivity and rate performance.

[0093] In a fifth aspect, the present invention provides an electronic device comprising the battery of the fourth aspect.

[0094] The present invention is not limited to the specific types of electronic devices, and may include electric vehicles, mobile phones, smart homes, robots, drones, electronic cigarettes, speakers, and any other devices that require battery components to power them.

[0095] Hereinafter, a positive electrode material provided by the present invention is introduced in detail through specific embodiments.

[0096] Example 1

[0097] (1) Take 0.05 g of lithium iron phosphate in a mortar, grind it thoroughly until it is uniform, add 0.3 g of cysteine ​​and grind it until there are no particles, add 1.2 g of phytic acid and continue grinding until the color of the mixture changes from purple to brown colloid, transfer the colloid to a drying oven at 80° C. for pre-curing treatment for 45 minutes to obtain a positive electrode material precursor;

[0098] (2) The cathode material precursor was placed in a tube furnace, heated to 600° C. at a rate of 10° C. / min in a N 2 atmosphere, calcined at 600° C. for 2 h, and naturally cooled to room temperature to obtain the cathode material.

[0099] The maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 100 μm, the thickness of the three-dimensional solid foam graphene layer is 0.33 nm, and the specific surface area of ​​the positive electrode material is 46.394 m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​1:30.

[0100] Example 2

[0101] The difference between this embodiment and embodiment 1 is that in step (1), the mass ratio of the positive electrode active material matrix to cysteine ​​and phytic acid is 1:4:24.

[0102] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 70μm, the thickness of the three-dimensional solid foam graphene layer is 0.301nm, and the specific surface area of ​​the positive electrode material is 32.280m 2 g -1 The mass ratio of the three-dimensional solid foam graphene layer to the positive electrode active material matrix is ​​1:35.

[0103] Example 3

[0104] The difference between this embodiment and embodiment 1 is that in step (1), the mass ratio of the positive electrode active material matrix to cysteine ​​and phytic acid is 1:5:24.

[0105] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 76μm, the thickness of the three-dimensional solid foam graphene layer is 0.315nm, and the specific surface area of ​​the positive electrode material is 35.467m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​1:34.

[0106] Example 4

[0107] The difference between this embodiment and embodiment 1 is that in step (1), the mass ratio of the positive electrode active material matrix to cysteine ​​and phytic acid is 1:6:20.

[0108] The closed cavity size of the three-dimensional solid foam graphene layer in the positive electrode material is 81 μm, the thickness of the three-dimensional solid foam graphene layer is 0.33 nm, and the specific surface area of ​​the positive electrode material is 38.251 m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​1:38.

[0109] Example 5

[0110] The difference between this embodiment and embodiment 1 is that in step (1), the mass ratio of the positive electrode active material matrix to cysteine ​​and phytic acid is 1:6:30.

[0111] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 73μm, the thickness of the three-dimensional solid foam graphene layer is 0.31nm, and the specific surface area of ​​the positive electrode material is 32.251m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​1:38.

[0112] Example 6

[0113] The difference between this embodiment and embodiment 1 is that in step (1), the temperature of the pre-curing treatment is 60°C.

[0114] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 92μm, the thickness of the three-dimensional solid foam graphene layer is 0.34nm, and the specific surface area of ​​the positive electrode material is 42.36m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​1:30.

[0115] Example 7

[0116] The difference between this embodiment and embodiment 1 is that in step (1), the pre-curing treatment time is 60 minutes.

[0117] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 95.2μm, the thickness of the three-dimensional solid foam graphene layer is 0.35nm, and the specific surface area of ​​the positive electrode material is 45.282m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​1:30.

[0118] Example 8

[0119] The difference between this embodiment and embodiment 1 is that in step (2), the calcination temperature is 500°C.

[0120] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 98μm, the thickness of the three-dimensional solid foam graphene layer is 0.36nm, and the specific surface area of ​​the positive electrode material is 48.3m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​1:30.

[0121] Example 9

[0122] The difference between this embodiment and embodiment 1 is that in step (2), the calcination treatment time is 3 hours.

[0123] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 102μm, the thickness of the three-dimensional solid foam graphene layer is 0.365nm, and the specific surface area of ​​the positive electrode material is 46.28m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​1:30.

[0124] Example 10

[0125] The difference between this embodiment and embodiment 1 is that in step (2), the heating rate of the calcination treatment is 5° C. / min.

[0126] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 83μm, the thickness of the three-dimensional solid foam graphene layer is 0.37nm, and the specific surface area of ​​the positive electrode material is 39.46m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​1:30.

[0127] Embodiment 11

[0128] The difference between this embodiment and embodiment 1 is that in step (2), the heating rate of the calcination treatment is 8°C / min.

[0129] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 86μm, the thickness of the three-dimensional solid foam graphene layer is 0.372nm, and the specific surface area of ​​the positive electrode material is 42.18m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​1:30.

[0130] Example 12

[0131] The difference between this embodiment and embodiment 1 is that in step (2), the atmosphere for calcination treatment is CO.

[0132] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 102.1, the thickness of the three-dimensional solid foam graphene layer is 0.34nm, and the specific surface area of ​​the positive electrode material is 45.281m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​1:30.

[0133] Embodiment 13

[0134] (1) 100 g of lithium iron phosphate and 7.5 g of glucose were mixed and ground to obtain a mixture, 0.4 g of sodium dodecyl sulfate, a foaming agent, was added to the mixture, mechanically stirred to dissolve it, and then rapidly stirred to foam it, to obtain a positive electrode material precursor;

[0135] (2) The cathode material precursor was placed in a tube furnace, heated to 500° C. at a rate of 5° C. / min in a N 2 atmosphere, calcined at 500° C. for 2 h, and naturally cooled to room temperature to obtain the cathode material.

[0136] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 112.3μm, the thickness of the three-dimensional solid foam graphene layer is 0.31nm, and the specific surface area of ​​the positive electrode material is 50.121m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​3:100.

[0137] Embodiment 14

[0138] The difference between this embodiment and embodiment 13 is that in step (1), the carbon source is polyethylene glycol.

[0139] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 115.2μm, the thickness of the three-dimensional solid foam graphene layer is 0.315nm, and the specific surface area of ​​the positive electrode material is 48.25m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​3:100.

[0140] Embodiment 15

[0141] The difference between this embodiment and embodiment 13 is that in step (1), the foaming agent is pentane.

[0142] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 109μm, the thickness of the three-dimensional solid foam graphene layer is 0.32nm, and the specific surface area of ​​the positive electrode material is 47.384m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​3:100.

[0143] Example 16

[0144] The difference between this embodiment and embodiment 13 is that in step (1), the foaming agent is azodicarbonamide.

[0145] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 106μm, the thickness of the three-dimensional solid foam graphene layer is 0.31nm, and the specific surface area of ​​the positive electrode material is 48.451m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​3:100.

[0146] Embodiment 17

[0147] The difference between this embodiment and embodiment 13 is that in step (1), the mass ratio of the positive electrode active material matrix to the carbon source and the foaming agent is 100:4:0.4.

[0148] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 111μm, the thickness of the three-dimensional solid foam graphene layer is 0.305nm, and the specific surface area of ​​the positive electrode material is 50.255m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​2:100.

[0149] Embodiment 18

[0150] The difference between this embodiment and embodiment 13 is that in step (1), the mass ratio of the positive electrode active material matrix to the carbon source and the foaming agent is 100:9:0.4.

[0151] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 114μm, the thickness of the three-dimensional solid foam graphene layer is 0.33nm, and the specific surface area of ​​the positive electrode material is 52.1m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​3.2:100.

[0152] Embodiment 19

[0153] The difference between this embodiment and embodiment 13 is that in step (1), the mass ratio of the positive electrode active material matrix to the carbon source and the foaming agent is 100:7.5:0.3.

[0154] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 108μm, the thickness of the three-dimensional solid foam graphene layer is 0.32nm, and the specific surface area of ​​the positive electrode material is 55.271m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​3:100.

[0155] Embodiment 20

[0156] The difference between this embodiment and embodiment 13 is that in step (1), the mass ratio of the positive electrode active material matrix to the semi-carbon source and the foaming agent is 100:7.5:0.5.

[0157] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 115μm, the thickness of the three-dimensional solid foam graphene layer is 0.34nm, and the specific surface area of ​​the positive electrode material is 51.362m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​3:100.

[0158] Embodiment 21

[0159] The difference between this embodiment and embodiment 13 is that in step (2), the calcination temperature is 500°C.

[0160] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 113μm, the thickness of the three-dimensional solid foam graphene layer is 0.36nm, and the specific surface area of ​​the positive electrode material is 55.28m 2 g -1The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​3:100.

[0161] Embodiment 22

[0162] The difference between this embodiment and embodiment 13 is that in step (2), the calcination treatment time is 1 hour.

[0163] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 108μm, the thickness of the three-dimensional solid foam graphene layer is 0.37nm, and the specific surface area of ​​the positive electrode material is 56.723m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​3:100.

[0164] Embodiment 23

[0165] The difference between this embodiment and embodiment 13 is that in step (2), the heating rate of the calcination treatment is 5°C / min.

[0166] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 102μm, the thickness of the three-dimensional solid foam graphene layer is 0.35nm, and the specific surface area of ​​the positive electrode material is 51.384m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​3:100.

[0167] Embodiment 24

[0168] The difference between this embodiment and embodiment 13 is that in step (2), the heating rate of the calcination treatment is 8°C / min.

[0169] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 104μm, the thickness of the three-dimensional solid foam graphene layer is 0.34nm, and the specific surface area of ​​the positive electrode material is 48.251m 2 g -1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​3:100.

[0170] Embodiment 25

[0171] The difference between this embodiment and embodiment 13 is that in step (2), the atmosphere for calcination treatment is CO.

[0172] Among them, the maximum size of the closed cavity of the three-dimensional solid foam graphene layer in the positive electrode material is 109μm, the thickness of the three-dimensional solid foam graphene layer is 0.35nm, and the specific surface area of ​​the positive electrode material is 50.251m 2 g-1 The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​3:100.

[0173] Comparative Example 1

[0174] (1) frosting and mixing a raw material system including 100 g of iron phosphate, 102 g of lithium phosphate (purity 98%), and 3 g of glucose (purity 10%) to obtain a mixture;

[0175] (2) The mixture was placed in a tube furnace, heated to 730° C. at a rate of 10° C. / min in a N 2 atmosphere, calcined at 730° C. for 8 h, and naturally cooled to room temperature to obtain a positive electrode material.

[0176] Test Example 1

[0177] The positive electrode materials prepared in the above embodiments and comparative examples were tested.

[0178] Among them, the conductivity test is carried out using the four-probe method, and the electronic conductivity of the positive electrode material is obtained according to the following formula:

[0179]

[0180] Where ρ is the resistivity of the material (unit: Ω·mm), and σ is the conductivity (unit: S / mm).

[0181] The first discharge specific capacity and rate performance are tested for the button cell according to GB / T 42161-2022; the preparation method of the button cell comprises the following steps:

[0182] The positive electrode materials prepared in the above embodiments and comparative examples are mixed with carbon black, PVDF and NMP in a mass ratio of 90:5:5:130, coated with aluminum foil to obtain a positive electrode sheet with a compaction density of 2.1, the negative electrode sheet is a lithium sheet, the electrolyte includes a lithium salt (LiPF6) and a solvent (EC+EMC+DMC), and the positive electrode sheet, the separator, the electrolyte, and the negative electrode are assembled into a button battery (the battery specification is 20 mm diameter and 2.5 mm thickness); in a 25°C environmental cabinet, after 3 cycles of 0.1C charge and discharge, 0.5C constant current and constant voltage charging is adopted, and 0.5C, 1C, 2C, 5C, and 10C constant current discharge are adopted, and the percentage of 0.5C, 1C, 2C, 5C, and 10C constant current discharge in the third discharge specific capacity is calculated, which is the coulomb efficiency at this rate.

[0183] The above test results are shown in Table 1.

[0184] Table 1

[0185]

[0186]

[0187] The preparation method provided by the present invention is used to perform in-situ carbon coating on the positive electrode active material matrix to form a three-dimensional solid foam-like graphene layer to realize a fully covered conductive network, and the positive electrode active material matrix is ​​comprehensively coated on the surface, thereby improving the conductivity and rate performance of the positive electrode material.

[0188] Test Example 2

[0189] The cathode material prepared in Example 1 was characterized by SEM, and the Figure 1 .

[0190] Depend on Figure 1 It can be seen that the graphene layer presents a three-dimensional solid foam, forming a conductive network. The lithium iron phosphate is evenly coated in the graphene layer, and the coating is tighter, achieving comprehensive "face-to-point" coating.

[0191] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A positive electrode material, characterized in that: The invention comprises a positive electrode active material matrix and a three-dimensional solid foamed graphene layer, wherein the three-dimensional solid foamed graphene layer has a closed cavity, and the positive electrode active material matrix is ​​accommodated in the closed cavity.

2. The positive electrode material according to claim 1, characterized in that The thickness of the three-dimensional solid foamed graphene layer is 0.3-0.4 nm.

3. The positive electrode material according to claim 1 or 2, characterized in that The maximum size of the closed cavity is 50-150 μm.

4. The positive electrode material according to claims 1-3, characterized in that: The specific surface area of ​​the positive electrode material is 20 to 50 m 2 / g.

5. The positive electrode material according to any one of claims 1 to 4, characterized in that The mass ratio of the three-dimensional solid foamed graphene layer to the positive electrode active material matrix is ​​1:(20-40).

6. The positive electrode material according to any one of claims 1 to 5, characterized in that The positive electrode active material matrix includes at least one of lithium metal phosphate and lithium transition metal oxide; Wherein, the general chemical formula of the lithium metal phosphate is LiMPO4; M is selected from at least one of Fe, Co, Ni, Cr, and Zn; The general chemical formula of the lithium transition metal oxide is Li 1+a [Ni x Co y M 1 z M 2 w ] 1-a O2; 0≤a≤0.2, 0.3≤x≤1, 0≤y≤0.4, 0≤z≤0.4, 0≤w≤0.1, and x+y+z+w=1, M 1 At least one selected from Mn and Al, M 2 At least one selected from Al, Ti, Mg, Zr, W, Y, Sr, Co, F, Si, Na, Cu, Fe, Ca, S and B.

7. A method for preparing the positive electrode material according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) mixing and grinding a raw material system including a cathode active material matrix, cysteine ​​and phytic acid to obtain a uniformly mixed and viscous brown colloid, and pre-curing the colloid to obtain a cathode material precursor; (2) calcining the positive electrode material precursor to obtain the positive electrode material.

8. The preparation method according to claim 7, characterized in that: The mass ratio of the positive electrode active material matrix to cysteine ​​and phytic acid is (1): (4-6): (20-30); and / or, The pre-curing treatment temperature is 60-80°C and the time is 10-30 minutes; and / or, The calcination treatment temperature is 500-600° C., the time is 2-3 hours, the heating rate is 5-10° C. / min, and the calcination atmosphere includes at least one of N2 and H2.

9. A method for preparing the positive electrode material according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) grinding a positive electrode active material matrix and a carbon source, adding a foaming agent, and mechanically stirring to generate bubbles, and then standing and pre-curing to obtain a positive electrode material precursor; (2) The positive electrode material precursor is calcined at a temperature of 500-800° C. for 1-2 hours to obtain the positive electrode material.

10. The preparation method according to claim 9, characterized in that: The carbon source is selected from at least one of glucose and polyethylene glycol.

11. The preparation method according to claim 9 or 10, characterized in that: The foaming agent includes at least one of a physical foaming agent, a surfactant foaming agent or a chemical foaming agent.

12. The preparation method according to claim 11, characterized in that: The physical foaming agent includes at least one of N2 and Co; and / or, The surfactant foaming agent includes at least one of rosin soap foaming agents, plant and animal protein foaming agents, sodium dodecyl sulfonate, and sodium polyoxyethylene fatty alcohol ether sulfate; and / or, The chemical foaming agent includes at least one of an azo compound, an N-nitroso compound and a hydrazide compound.

13. The preparation method according to claim 9 or 10, characterized in that: The foaming agent is a solid foaming agent or a liquid foaming agent, wherein the sublimation point of the solid foaming agent is 70-100°C, and the boiling point of the liquid foaming agent is less than 110°C.

14. The preparation method according to claim 13, characterized in that: The solid foaming agent includes at least one of azodicarbonamide and sodium α-olefin sulfonate; the liquid foaming agent includes at least one of pentane and hexane.

15. The preparation method according to any one of claims 9 to 14, characterized in that: The mass ratio of the positive electrode active material matrix to the carbon source and the foaming agent is (100): (2-5): (0.3-0.8); and / or, The pre-curing treatment temperature is 25-70°C and the time is 30-60 minutes; and / or, The calcination treatment temperature is 500-800°C, the time is 1-2h, the heating rate is 5-10°C / min, and the calcination atmosphere includes at least one of N2 and CO.

16. A positive electrode sheet, characterized in that: The positive electrode material comprises the positive electrode material according to any one of claims 1 to 6 or the positive electrode material prepared by the preparation method according to claims 7 to 15.

17. A battery, characterized in that: Including the positive electrode sheet as described in claim 16.

18. An electronic device, characterized in that: Comprising the battery of claim 17.

Citation Information

Patent Citations

  • Continuous-phase spongy graphene material as well as preparation method thereof

    CN103794791A

  • Graphene foam-protected metal fluoride and metal chloride cathode active materials for lithium batteries

    CN110366792A

  • Three-dimensional graphene / metal precursor / MOF composite material and preparation method and application thereof

    CN110783573A

  • Preparation method of gradient macroporous conductive composite hydrogel for flexible strain sensor

    CN114621497A

  • Negative electrode, preparation method thereof and electrochemical device

    CN118073517A